Environmental social work in the disciplinary literature, 1991–2015. (May 2020) - Krings, Amy; Victor, Bryan G; Mathias, John; Perron, Brian E
Despite increasing acknowledgment that the social work profession must address environmental concerns, relatively little is known about the state of scholarship on environmental social work. This study provides a scientometric summary of peer-reviewed articles ( N  = 497) pertaining to environmental topics in social work journals between 1991 and 2015. We find that theoretical and empirical scholarship on environmental social work is growing, though this growth remains limited to specific geographical regions and topics. We note the need to clarify the relationship between environmental social work as a theoretical paradigm and as a research topic.